2023
DOI: 10.1186/s12916-023-02805-x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal and neonatal microbiota in pregnant women with preterm premature rupture of membranes and consecutive early onset neonatal sepsis

Abstract: Background Preterm premature rupture of membranes (PPROM), which is associated with vaginal dysbiosis, is responsible for up to one-third of all preterm births. Consecutive ascending colonization, infection, and inflammation may lead to relevant neonatal morbidity including early-onset neonatal sepsis (EONS). The present study aims to assess the vaginal microbial composition of PPROM patients and its development under standard antibiotic therapy and to evaluate the usefulness of the vaginal mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…Lactobacillus is the most dominant genus within the vaginal microbiome, and low counts of Lactobacillus have previously been stated to be indicative of increased PTB risk [5, 28]. Certain species of Anaerococcus are found to be associated with increased PTB risk [1], however, there are also reports that Anaerococcus may be a protective taxon against PTB [19]. There is strong evidence linking high Gardnerella vaginalis presence with PTB and bacterial vaginosis, which also increases PTB risk [44, 46].…”
Section: Resultsmentioning
confidence: 99%
“…Lactobacillus is the most dominant genus within the vaginal microbiome, and low counts of Lactobacillus have previously been stated to be indicative of increased PTB risk [5, 28]. Certain species of Anaerococcus are found to be associated with increased PTB risk [1], however, there are also reports that Anaerococcus may be a protective taxon against PTB [19]. There is strong evidence linking high Gardnerella vaginalis presence with PTB and bacterial vaginosis, which also increases PTB risk [44, 46].…”
Section: Resultsmentioning
confidence: 99%
“…Premature rupture of membranes (PROM), a process of spontaneous rupture of membranes before the onset of labor [57], is another adverse pregnancy closely associated with the imbalance of vaginal microbiota [58][59][60][61]. PPROM has closely related to maternal and neonatal morbidities, such as significantly lower birth weight and gestational age, earlyonset neonatal sepsis, funicity, endometritis, chorioamnionitis urinary tract infection, and postpartum bacteremia [58,62]. Infection is probably one of the most important mechanisms of PROM.…”
Section: Vaginal Microbiota and Premature Rupture Of Membranesmentioning
confidence: 99%
“…Richard G. B found that erythromycin treatment of vaginal microflora disorders in patients with PROM exacerbated vaginal dysbiosis, including Lactobacillus depletion and increased relative abundance of Sneathia and increased the risk of subsequent mycotic vaginitis and neonatal sepsis [13]. The disturbance of vaginal flora caused by antibiotic therapy may aggravate the occurrence of adverse conditions in the mother and fetus [13,62,108]. Therefore, individualized treatment and probiotics should be recommended instead of antimicrobial regimens alone to treat adverse outcomes caused by vaginal dysbiosis [102].…”
Section: Identify Pregnant Women At High Risk and Search For Effectiv...mentioning
confidence: 99%
“…10 BV or vaginal dysbiosis during pregnancy has been linked to several complications such as ascending bacterial infections, preterm birth, preterm premature rupture of membranes, and lower birth weight. 11 Interestingly, African and Hispanic women on average have a higher prevalence of Gardnerella, Atopobium, and Corynebacterium among other obligate and facultative bacterium that normally maintain a higher pH than Lactobacilli without clinical presentation of BV. 12 This suggests that the population of the bacterium may not be the sole factor in identifying or inducing vaginal dysbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to hormonal differences that regulate estrogen production and glycogen metabolism during pregnancy that promote a less‐diverse environment with reduced Lactobacilli abundance 10 . BV or vaginal dysbiosis during pregnancy has been linked to several complications such as ascending bacterial infections, preterm birth, preterm premature rupture of membranes, and lower birth weight 11 . Interestingly, African and Hispanic women on average have a higher prevalence of Gardnerella , Atopobium , and Corynebacterium among other obligate and facultative bacterium that normally maintain a higher pH than Lactobacilli without clinical presentation of BV 12 .…”
Section: Introductionmentioning
confidence: 99%